Self-Compassion and Procrastination Among First Born and Last Born University Students - Mamoona Ismail Loona, Mussarat Jabeen Khan (Pakistan Journal of Psychology, 2016)
The present study was intended: first to measure the predictive association between procrastination and self-compassion among first born and last born university students; second to assess the differences on the variable of procrastination between first born and last born university students. A sample of 200 students (100 boys and 100 girls) was taken from different universities of Islamabad and Rawalpindi. The Procrastination Scale (Lay, 1986) and Self-Compassion Scale (Neff, 2003) were used. The data was analyzed using Regression Analyses and t-test. The results showed that self-compassion and its sub-scales of isolation and mindfulness significantly predicted procrastination in first born university students. Further, self-compassion is found to be insignificant predictor of procrastination in last born university students whereas its sub-scale of kindness significantly predicted procrastination in last born university students. Furthermore, differences between the first born and last born university students on the variable of procrastination are found to be insignificant. Implications of the findings and avenues for future research are suggested